Mindfulness predicts insight in obsessive-compulsive disorder over and above OC symptoms: An experience-sampling study. (October 2019) - Landmann, Sarah; Cludius, Barbara; Tuschen-Caffier, Brunna; Moritz, Steffen; Külz, Anne Katrin
Abstract: Insight in obsessive-compulsive disorder (OCD) is assumed to fluctuate over time. However, temporal variations of insight and its correlates in OCD have never been empirically studied. We used ecological momentary assessment (EMA) to analyze the temporal variation of insight into the unreasonableness of the threat-related core belief (1), into the senselessness of compulsions to prevent this belief from occurring (2), and into the belief, itself, as being due to OCD (3). Furthermore, we analyzed whether worry, self-punishment and mindfulness are associated with these aspects of insight. A total of 50 OCD patients underwent EMA 10 times a day over 6 consecutive days. Data were analyzed using multilevel modelling. Results revealed that multiple time-points within individuals accounted for up to 51.4% of insight variance, indicating a substantial fluctuation of insight over time. Root mean square successive difference (rMSSD) scores indicated significantly higher fluctuation patterns in the doubt/checking dimension as compared to taboo thoughts throughout all aspects of insight. As hypothesized, self-punishment and mindfulness significantly predicted insight into the unreasonableness of the threat-related belief and the senselessness of compulsions to prevent this belief from occurring. Mindfulness demonstrated the greatest predictive value and remained significant after controlling for OC symptoms. Contrary to expectation, worry, as it was measured in our study, was not associated with insight. Besides providing evidence for insight fluctuation, our results indicate that mindfulness-based strategies might be beneficial for increasing insight in OCD. Highlights: Insight in OCD is a dynamic process which fluctuates over time. Intensity of insight fluctuation differs significantly between OC symptom dimensions. Self-punishment predicts lower insight, whereas mindfulness predicts higher insight. Mindfulness remains a significant predictor of insight even after controlling for OC symptoms. Results indicate the potential benefit of mindfulness for improving insight in OCD.